Detection of Torque Teno Virus (TTV) and TTV-Like Minivirus in patients with presumed infectious endophthalmitis in India. - Poonam Naik; Vivek Pravin Dave; Joveeta Joseph (PLoS ONE)
Human anelloviruses (Torque Teno Virus (TTV) and TTV Like Mini Virus (TLMV)) are now being reported at a high prevalence across the world, with a controversial disease-inducing potential. The aim of this study was to investigate the role of these anellovirus in vitreous of patients with presumed infectious endophthalmitis. After informed consent, vitreous fluid from patients with endophthalmitis (n = 103) and non-infectious pathologies (n = 102) were analyzed for the presence of TTV and TLMV DNA by qPCR with the limit of quantification defined as 100 copies per reaction. Among the patients clinically diagnosed with endophthalmitis, 29 of the 40 culture proven samples (72.5%) and 42 out of 63 (66.6%) of culture-negative samples were positive for presence of TTV/TLMV. Interestingly, 51 of the 102 (50%) samples in the control group were also positive for TTV/TLMV. Comparing the clinical outcome among patients diagnosed with endophthalmitis, we observed no significant association in the final visual acuity of patients who were positive for presence of TTV/TLMV, however, these patients had significantly higher repeat antibiotic injections (p = 0.03). Further evidence is however needed to correlate TTV / TLMV with a particular pathology or group of pathologies in the eye.